Capacity Mechanisms in the European Context: Can we ensure internal market synergies? - Karsten Neuhoff; Sebastian Schwenen (DIW - Deutsches Institut für Wirtschaftsforschung, 2014)
Using generating and demand resources across national borders brings synergies and improves supply adequacy in Europe as a whole. However, national capacity remuneration mechanisms (CRMs) may pose barriers for the participation of energy resources across borders. This ultimately challenges the idea of a common internal market. Given the current experience with the newly imposed CRMs, indeed the integration of foreign capacities seems challenging as certain regulatory requirements, for instance on interconnector capacity, have to be met. Although all current CRMs in the EU are explicitly of temporary nature, given the current divergence in EU power market design, the question will be not whether but how to agree and coordinate on different forms of capacity remuneration in the EU for the years to come.
Keywords: 330